MENGENAL SISI LAIN POHON MAYANG BAGI KEHIDUPAN MANUSIA - Kaihena, Martha; Nusaly, Windy Natalia; Patty, Kristi Lenci; Salamena, Fuadiska; Manurung, Brian Saputra (Pattimura University, 2024)
The community service activity with the title